2012
DOI: 10.1186/1471-2407-12-91
|View full text |Cite
|
Sign up to set email alerts
|

EMT transcription factors snail and slug directly contribute to cisplatin resistance in ovarian cancer

Abstract: BackgroundThe epithelial to mesenchymal transition (EMT) is a molecular process through which an epithelial cell undergoes transdifferentiation into a mesenchymal phenotype. The role of EMT in embryogenesis is well-characterized and increasing evidence suggests that elements of the transition may be important in other processes, including metastasis and drug resistance in various different cancers.MethodsAgilent 4 × 44 K whole human genome arrays and selected reaction monitoring mass spectrometry were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
271
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(290 citation statements)
references
References 46 publications
16
271
2
1
Order By: Relevance
“…Previous studies reported that cancer cells could acquire new traits such as enhanced proliferation and drug resistance through EMT (Sarkar et al, 2009;Singh and Settleman, 2010;Haslehurst et al, 2012). We also found that ltDSCs had higher colony forming ability than parental cells.…”
Section: Ltdscs Were More Malignant Compared To Parental Cellssupporting
confidence: 70%
“…Previous studies reported that cancer cells could acquire new traits such as enhanced proliferation and drug resistance through EMT (Sarkar et al, 2009;Singh and Settleman, 2010;Haslehurst et al, 2012). We also found that ltDSCs had higher colony forming ability than parental cells.…”
Section: Ltdscs Were More Malignant Compared To Parental Cellssupporting
confidence: 70%
“…In another study, overexpression of Snail was shown to be correlated with a higher state or to be a marker of poor prognosis in malignancies because it confers resistance to apoptosis induced by DNA damage (36,37). In ovarian cancer cell lines, upregulation of Snail and Slug has been correlated with resistance to radiation and paclitaxel and shown to participate directly in p53-mediated pro-survival signaling (38). Twist has been found to be expressed at high levels in a number of human cancers, including those of the breast, prostate, esophagus, and uterus, and is associated with EMT and intravasation (39).…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al (27) reported that the expression of EGFL7 in gastric cancer cells promotes the epithelial-to-mesenchymal transition (EMT) and tumor metastasis by epidermal growth factor receptor (EGFR)-mediated protein kinase B (AKT) phosphorylation, which subsequently activates Snail and suppresses the transcription of E-cadherin. Numerous studies have demonstrated that increased EMT may lead to chemoresistance in bladder, lung, breast and ovarian cancers (28)(29)(30)(31)(32). In addition, Vega et al (33) reported that Snail inhibits the cell cycle and confers resistance to TGF-β-induced cell death, consistent with Snail activating the Mek/Frk and PI3K/Akt survival pathways.…”
Section: Introductionmentioning
confidence: 80%
“…The second hypothesis was that the promotion of EMT by EGFL7 may induce the development of tumor cell resistance to chemotherapy; EMT is regulated by EGFR-mediated AKT phosphorylation induced by EGFL7, which then activates Snail and the subsequent suppression of E-cadherin transcription (27). Numerous studies have previously reported that EMT may have a function in acquired chemoresistance (28)(29)(30)(31)(32). The third hypothesis considered that EGFL7 may have a role in the development of tumor chemoresistance through an increased resistance to cell apoptosis induced by the activation of Snail.…”
Section: No Of Patients --------------------------------------------mentioning
confidence: 99%